Solid index versus intraoral scanners in the full-arch implant impression: in vitro trueness evaluation - Francesco Guido Mangano; Matteo Bonacina; Federico Mandelli; Fabio Marchiori (BMC Research Notes, 2020)
Abstract Objectives To assess the trueness of a solid index (SI) in the full-arch (FA) implant impression, and to compare it with that of two intraoral scanners (IOSs). A type-IV gypsum model of a completely edentulous patient with 8 implant scanbodies (SBs) was scanned with a desktop scanner (7Series®) to obtain a reference virtual model (RVM), and with two IOSs (CS 3700® and Emerald S®). Five scans were taken with each IOS. Based on the RVM, an SI (custom tray consisting of hollow cylinders connected by a bar) was fabricated and used to capture a physical impression of the model; from this, a second gypsum model was derived and scanned with a desktop scanner (D15®). The SI-derived and the IOSs-derived models were superimposed onto the RVM, to evaluate trueness. Results The overall mean trueness was 29 μm (± 26) for the SI-derived model, versus 42.4 μm (± 14.7) for CS 3700® and 52.2 μm (± 4.6) for Emerald S®. Despite its limitations (in vitro design, a limited number of models evaluated, RVM captured with a desktop scanner) this study supports the use of SI for FA implant impressions. Further studies are needed to confirm this evidence.